2010
DOI: 10.3109/02841850903280508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clenching on t2 and diffusion parameters of the masseter muscle

Abstract: The coefficients for diffusion of the MM were sensitive to change by clenching, and lambda(2) was the most sensitive. Moreover, the relative distribution of the bite forces had no effect on any of the indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Chikui et al 21 showed that the variation of bite force had no influence on the diffusion parameters of the masseter muscle. In this study, there is no method for conducting the chewing and for monitoring the bite force during MRI examination; therefore, this study focused on the effect of the distribution of the bite force by static clenching in the intercuspal position on the diffusion parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chikui et al 21 showed that the variation of bite force had no influence on the diffusion parameters of the masseter muscle. In this study, there is no method for conducting the chewing and for monitoring the bite force during MRI examination; therefore, this study focused on the effect of the distribution of the bite force by static clenching in the intercuspal position on the diffusion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to intolerability of some volunteers to the discomfort caused by the opening aid device, only 23 volunteers underwent the 3D BRAVO sequences with their mouth opened. The 15 min of jaw rest before the entire MR examination and the 15 min of jaw rest between the second and third DTI acquisitions was determined by the previous study performed by Chikui et al 21 …”
Section: Methodsmentioning
confidence: 99%
“…The authors previously demonstrated that an MTC imaging technique strongly reflects the masticatory muscle edematous changes, possibly leading to masseter muscle pain, but not TMJ pain [27]. MRS and diffusion tensor imaging provide information on muscle metabolism associated with masticatory muscle pain and fatigue [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, MR sequences such as magnetization transfer contrast (MTC) imaging [27], magnetic resonance spectroscopy (MRS) [28], diffusion tensor imaging [29], and ultrasonography [30] have been applied to evaluate associated masticatory muscular pathological changes such as edema and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients for diffusion of the masseter muscles are sensitive to change by clenching—one possible cause of TMDs [120]. In the future, the relationship between the diffusion coefficients and pain symptoms in the masticatory muscles should be elucidated.…”
Section: Myositis and Muscle Edema/contracture-related Myofascial Paimentioning
confidence: 99%